ANALISIS KOMPOSISI DAN KEPADATAN SPESIES GULMA PADA PERKEBUNAN KELAPA SAWIT (ELAEIS GUINEENSIS JACQ.) DI KEBUN ITSI - Parasian Simanjuntak; Nursalimah Pardosi; Andreas Sembiring; Zahra Hamdani Sitorus; Noah Theo Filus Sitorus; Risky Ramadan; Alvi Zidan Fahrozi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Oil palm (Elaeis guineensis Jacq.) is a major plantation commodity that plays an important role in supporting the economy. One of the main constraints in improving its productivity is the presence of weeds, which compete with crops for essential growth resources. This study aimed to identify the composition of weed species and analyze their dominance level in the practice field of Institut Teknologi Sawit Indonesia (ITSI), Medan. The research applied a quadrat method using plots of 1.5 m × 1.5 m, which were further divided into four sub-plots, while species identification was carried out using the PlantNet application. The observed parameters included relative density and relative frequency. The results revealed that six weed species were recorded, with Axonopus compressus identified as the most dominant species, followed by Synedrella nodiflora and Asystasia gangetica. These findings provide a basis for developing effective and sustainable weed management strategies.